UNJUK KERJA HIDROGRAF SATUAN SINTETIK NAKAYASU, ITB 2 DAN LIMANTARA UNTUK DAERAH ALIRAN SUNGAI BERBENTUK MEMANJANG - Humairo Saidah; Agustono Setiawan; Lilik Hanifah; Agus Suroso; Anid Supriyadi (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
Estimated flood discharge value for water structure design, ideally determined based on the frequency analysis of measured discharge data. However, the measured discharge data is often not recorded or if the length is limited. So, it needs the technique in getting the design flood value from rain data through the Synthetic Unit Hydrograph (SUH) method. This study examined the suitability of the three (3) SUH methods (Nakayasu, Limantara and ITB2) in generating the design flood discharge and compared it with the Observed Unit Hydrograph (OUH) of the elongated shape watersheds, namely Sidutan and Reak. The main values that are compared are peak discharge, peak time, and base time of HSS to the HSO value. The results obtained from the Sidutan watershed and the Reak watershed are both elongated shape watershed, have almost the same length as the main river, but the area of the Sidutan watershed is greater than Reak watershed. The average OUH of both watersheds indicated that both Qp and Tb of the Sidutan watershed are greater than Reak, but the time peak hydrograph (Tp) was reached at almost the same time. The SUH method that produced unit hydrographs closest to OUH is Nakayasu, then ITB2 and Limantara, respectively.